3D phosphorus-carbon electrode with aligned nanochannels promise high-areal-capacity and cyclability in lithium-ion battery - Yan, Yuhua; Xu, Hongyi; Peng, Chengxin; Zhang, Pengcheng; Yang, Junhe; Zheng, Shiyou (Applied surface science, 2019)
Despite of poor electrical conductivity and large volume expansion, low mass loading of phosphorus-based electrode severely decrease overall gravimetric/volumetric energy density, impeding its practical application in lithium ion batteries (LIBs). Herein, we construct a high-areal-capacity P@rGO-ACW electrode by warping phosphorus with rGO and confining in 3D microchanneled carbon matrix (P@rGO-ACW). The conductive 3D carbon scaffold (ACW) derived from natural wood acts as integrated porous current collector to accelerate the electrons/ions transport, while the vertical-alignment microchannels confine phosphorus and accommodate its volume expansion. The unique feature of phosphorus‑carbon electrode with 3D aligned nanochannels allows for a considerable improvement in high-areal-capacity and cyclability even in case of high mass loading. As expected, the P@rGO-ACW electrode can deliver a superior lithium storage capacity of 12.5 Ah cm−2 at a current of 0.5 mA cm−2 and a stable cycling performance of 9.5 Ah cm−2 at 1.0 mA cm−2 with a phosphorus mass loading of 16.6 mg cm−2. Our approach provides a versatile methodology to explore high mass-loading electrode towards developing high energy LIBs. [Display omitted] •ACW with vertically aligned microchannels ensure high electronic/ionic conductivity.•The 3D P@rGO-ACW electrode with aligned nanochannels can confine phosphorus and accommodate its volume expansion.•The P@rGO-ACW electrode delivers a superior capacity of 12.5 Ah cm-2 with a high phosphorus mass loading of 16.6 mg cm-2.